Starting well or losing their way? : the position of youth in the labour market in OECD countries - Quintini, Glenda [Verfasser]; Martin, Sebastien [Verfasser] (My University, 2006)
"Despite the fact that today's young cohorts are smaller in number and better educated than their older counterparts, high youth unemployment remains a serious problem in many OECD countries. This reflects a variety of factors, including the relatively high proportion of young people leaving school without a basic educational qualification, the fact that skills acquired in initial education are not always well adapted to labour market requirements, as well as general labour market conditions and problems in the functioning of labour markets. The paper highlights the trends in youth labour market performance over the past decade using a wide range of indicators. It also presents new evidence on i) the length of transitions from school to work; ii) the wages, working conditions and stability of jobs performed by youth; and iii) the degree of so-called 'over-education', i.e. the gap between the skills of young people and the jobs they get." (author's abstract, IAB-Doku) ((en))
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 1.3.2.2 Übergänge; OECD; Arbeitsmarkt; Berufseinmündung; Arbeitsloser Jugendlicher; Überqualifikation; Unterqualifikation